2021
DOI: 10.1080/14631377.2021.1943912
|View full text |Cite
|
Sign up to set email alerts
|

One transition story does not fit them all: initial regional conditions and new business formation after communism

Abstract: We investigate the reasons for the pronounced regional differences of new business formation after the transformation from a centrally planned system to a market economy in East Germany. Relatively high start-up rates are found in regions that had a well-qualified workforce and a relatively high share of self-employment left over at the end of the communist period. This also holds for high-tech manufacturing start-ups. Based on our conclusion that policy should account for these initial regional conditions, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This study is important as it brings together several factors named by Reynolds et al (2002Reynolds et al ( , 2005 as important drivers of entrepreneurial activity in developed countries, which were found to be also valid and strong for entrepreneurship in Russia. In addition to factors traditionally described conducive to entrepreneurship (Fritsch et al 2021(Fritsch et al , 2022Fritsch and Storey, 2004) it is the market potential of a region, quality of formal institutions and the reduction in administrative burden and taxes, tax benefits, special economic zones that facilitate original development and finally the digital infrastructure for entrepreneurs and their access to the Internet. Interestingly, this study demonstrated that the market potential of a region matters, and it's likely to a greater extent for countries with a smaller size than for Russia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is important as it brings together several factors named by Reynolds et al (2002Reynolds et al ( , 2005 as important drivers of entrepreneurial activity in developed countries, which were found to be also valid and strong for entrepreneurship in Russia. In addition to factors traditionally described conducive to entrepreneurship (Fritsch et al 2021(Fritsch et al , 2022Fritsch and Storey, 2004) it is the market potential of a region, quality of formal institutions and the reduction in administrative burden and taxes, tax benefits, special economic zones that facilitate original development and finally the digital infrastructure for entrepreneurs and their access to the Internet. Interestingly, this study demonstrated that the market potential of a region matters, and it's likely to a greater extent for countries with a smaller size than for Russia .…”
Section: Discussionmentioning
confidence: 99%
“…We do not include the category of sole proprietorships 2 and self-employed, who belong to the informal sector in Russia as it is impossible to track them by region. We argue that the use of regional fixed effects may partly account for the size of the informal sector as entrepreneurship activity, including informal entrepreneurship that demonstrates regional persistence (Fritsch et al 2021). The geographical distribution of small enterprises in Russia has been shaping for the last 30 years.…”
Section: Variables Dependent Variablementioning
confidence: 91%
“…showed high levels of new business formation after reunification (Fritsch et al, 2021c). document another striking example of persistent entrepreneurship that experienced even stronger disruptions than East Germany.…”
Section: Micro and Small Businessesmentioning
confidence: 99%
“…Recent research for the case of Germany has shown that the recovery of entrepreneurship after the demise of the communist regime was stronger in regions that had an entrepreneurial culture and relatively high remaining levels of selfemployment (Wyrwich, 2012;Fritsch et al 2021c). One explanation for such survival of regional entrepreneurial tradition could be that people in these regions used the leeway that the institutional framework allowed for self-employment more frequently.…”
Section: Formal Institutionsmentioning
confidence: 99%
“…Higher education positively influences labor productivity, which ensures entrepreneurial success. As a determinant of new firm formation, education (especially tertiary education), was found to be statistically significant in numerous empirical studies [20,33,34]. Since the results depend on location and time, there are also studies that did not find education to be statistically significant for the birth of new enterprises [13,16].…”
Section: Educationmentioning
confidence: 99%